Influence of the aesthetic model and body dissatisfaction in adolescent females of a State educational institution of Lima east, 2016 - Agesto Pinaud, Jhonny (2019)
Objective: To determine the relationship between the influences of the aesthetic model and body dissatisfactionin adolescent females from 3rd to 5th of high school of a state educational institution of east Lima, 2016.Materials and methods: The design of this study is non-experimental, cross sectional and of a correlationalscope. To achieve this, a sample of 255 female students whose ages ranged from 13 to 17 years old, who weresubmitted to the Aesthetic Model Influences Questionnaire (CIMEC) and Body Shape Questionnaire (BSQ)were used. Results: They were obtained through Spearman’s correlation coefficient, showing a highly significantrelationship between the influence of the aesthetic model and body dissatisfaction (rho =, 785 **, p <0.000). Bythe same token, the relationship between the dimensions of influences of the aesthetic model and the variable ofbody dissatisfaction are significant. Conclusions: The greater the influence of the beauty model, the greater theconcern will be for the body image and weight in adolescents.